Correlação entre o exame clínico, a mamografia e a ultra-sonografia com o exame anátomo-patológico na determinação do tamanho tumoral no câncer de mama - Fernanda Monteiro de Paula Siqueira (2006)
PURPOSE: The purpose of the study was to evaluate witch method between clinical examination, mammography and ultrasonography, provides the most accurate measurement of the tumor size in breast cancer, using as reference, the pathologic exam. METHODS: One hundred and eighty four malign cases among 245 patients with suspectbreast lesions were evaluated at the Masthology Service of the Hospital das Clínicas da UFMG between August, 1997 and August, 2000. The maximum tumor diameter was assessed by clinical examination, mammography and ultrasonography and correlated to the maximumdiameter estimated by post surgical pathologic exam. The Pearsons correlation coefficient was used to analyze the correlation. RESULTS: The Pearsons correlation coefficient between the pathologic exam and clinical evaluation was 0.80; between the pathologic exam and mammography was 0.75 and between the pathologic exam and ultrasonography was 0.77 (p < 0.05). CONCLUSION: The clinical examination, mammography and ultrasonography demonstrateda high correlation with the pathological tumor size and are equivalent as methods to the determination of breast cancer size.